Six essential elements of leadership : Marine Corps wisdom of a Medal of Honor recipient - Fox, Wesley L. (Naval Institute Press, 2011)
Col. Wesley Fox is a Medal of Honor recipient who wrote two widely respected accounts of his wartime experiences in the Marine Corps. His books, Marine Rifleman: Forty-Three Years in the Corps and Courage and Fear: A Primer, are both considered classic war memoirs. Drawing on over four decades of leadership experience, both during two wars and peacetime, Fox insists that a good leader must focus on building an organization based on the bonds of comradeship. Successful leaders are those who are actively concerned with the health, happiness, and daily lives of those who follow them. He contends.